World War II heroes - Zullo, Allan (New York : Scholastic, 2007)
Collects ten tales of American heroes who served in World War II.
Chief Petty Officer John Finn -- Private First Class Jack Lucas -- Lieutenant Richard Antrim -- Commander Lawson "Red" Ramage -- Private First Class Desmond Doss -- Sergeant Forrest "Woody" Vosler -- Lieutenant Colonel James Rudder -- Captain Matt Urban -- Sergeant Maynard "Snuffy" Smith -- Second Lieutenant Vernon Baker.
6.8
3-6
Keywords: World War, 1939-1945 -- Personal narratives -- Juvenile literature; Soldiers -- United States -- Juvenile literature; Heroes -- Biography -- Juvenile literature; World War, 1939-1945 -- Personal narratives; Soldiers; Heroes; World War, 1939-1945 -- Personal narratives; Soldiers; Heroes and heroines -- Biography; United States -- Armed Forces -- Juvenile literature; United States -- Armed Forces; United States -- Armed Forces